AN EVALUATION OF THE TRADITIONAL SPORTS FESTIVAL PROGRAM AT THE NATIONAL LEVEL - Alfredo Do Karmo; James Tangkudung; Moch. Asmawi (Program Pascasarjana Universitas Negeri Jakarta, 2019)
Traditional sports is a game of people who live in a society that has taken root, grow and thrive and has been passed down from generation to generation, based on it should be backed by the consistency and seriousness of the government for managing it. These conditions encourage Traditional Sports Field, Assistant Deputy Sports Recreation, Deputy civilizing Sports, Kemenpora (the Ministry of Youth and Sports) do excavation, standardization, preservation and development through the organization Traditional National Sports Festival, The evaluation of the festival program should be done to improve the quality of the program.This study is a CIPP (Context, Input, Process, Product) evaluation model developed by Stufflebeam. It’s evaluation shows that: 1) context evaluation, The vision, mission and goals is very good and legal basis is enough and analysis of needs is very good. 2) Input evaluation includes, the planning strategy, support the organizers and criteria for participants is good, support area and support fund is enough. 3) Process evaluation include, preparation, implementation and monitoring system is good. 4) Product evaluation include, achievement of participation is good and result of the implementation of Program of Traditional National Sports Festival is enough. Keyword: an evaluation of the traditional sports festival program, CIPP (Context, Input, Process, Product) Evaluation Models.